Resources Mapping of Elementary School Educators in Central Jakarta - Hamid Al Jufri (International Journal of Social Service and Research, 2023)
The problem of this research is that there are still many teachers who are not yet professional because teachers are the spearhead of a nation's progress. The purpose of this research is to find out the level of education, status, certification, and age of elementary school teachers in Central Jakarta. The population in this study were all teachers in Central Jakarta. Data collection techniques were carried out by means of documentation and questionnaires. In order to get an accurate assessment, the assessment of the results of the questionnaire is carried out with a descriptive quantitative assessment. The results showed that there were still many teachers with 1486 senior high school levels, 1588 assistant and honorary teachers, and 1847 who were not certified, and there was still a lack of young teachers. Based on the results of this study, it is suggested that public schools in Central Jakarta need to increase the level, status, and certification of teachers, and that there needs to be age consideration in accepting teachers.